A novel design for low insertion loss, multi-band RF-MEMS switch with low pull-in voltage - Mahesh Angira; KamalJit Rangra (Engineering Science and Technology, an International Journal, 2016)
This paper presents a new type of capacitive shunt RF-MEMS switch. In the proposed design, float metal concept is utilized to reduce the RF overlap area between the movable structure and central conductor of CPW for improving the insertion loss of the device. This has been achieved without affecting the down-state response. Further, float metal also makes the down-state behavior predictable in terms of resonant frequency. For reducing the pull-in voltage, the switch is implemented with cantilever type of structure on either side of the transmission line. This structure also has the capability to inductively tune the isolation optimum value to the different bands and thus can be used in the reconfigurable RF systems. The device shows an insertion loss less than 0.10 dB, a return loss below 36.80 dB up to 25 GHz as compared to 1.00 dB insertion, 7.67 dB return loss for the conventional switch. In the OFF state, proposed device shows two isolation peaks i.e. 48.80 dB at 4.5 GHz and 54.56 dB at 9.7 GHz, when either or both cantilevers are electro-statically actuated to the down-state position respectively. The conventional device has a single isolation peak in the X-band. In addition, improvement of around 3 times in the bandwidth has also been achieved. The designed switch can be used at device and sub-system level for the future multi-band communication applications.